2008
DOI: 10.1111/j.1468-1293.2008.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of their children's HIV status in HIV‐positive mothers attending a genitourinary medicine clinic in the UK

Abstract: Objectives To determine whether HIV‐infected mothers knew the HIV status of their children, enabling the offer of targeted testing of children at risk. Methods All HIV‐positive women attending the genitourinary medicine clinic at a district general hospital in the United Kingdom were asked whether they had children and the age, HIV status and residence of their children using a standardized proforma. Results A total of 297 HIV‐positive women were included in a prospective audit. Two hundred and fifty‐four wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Loss of status and community support and social isolation after confidentiality gaps are among the main reasons given for not testing 9–13 , 16 , 24 , 26 , 27 , 34 , 41 , 42 . This is a particular concern for individuals who need to bring a relative or friend to help with translation 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Loss of status and community support and social isolation after confidentiality gaps are among the main reasons given for not testing 9–13 , 16 , 24 , 26 , 27 , 34 , 41 , 42 . This is a particular concern for individuals who need to bring a relative or friend to help with translation 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Only 39% of children born to HIV‐positive mothers were untested, which is lower than reported in other studies from the UK [5]. Of these, 25% were 18 years of age or younger.…”
Section: Discussionmentioning
confidence: 73%
“…A recent BHIVA audit of 143 UK adult HIV clinics showed that only 61 (43%) had started or completed a review of their patients to identify and test children for HIV infection. In an earlier study of women with HIV infection attending a clinic in south‐east England, 51% of their children under 16 years old living in the UK and 91% living abroad were untested [5]. This study looked at the HIV testing status of children whose mothers attend HIV services at three south‐west London clinics.…”
Section: Introductionmentioning
confidence: 99%
“…This is not uncommon amongst African parents who live in the UK (Eisenhut et al 2008 ) and particularly for children who live in Africa. This is not uncommon amongst African parents who live in the UK (Eisenhut et al 2008 ) and particularly for children who live in Africa.…”
Section: Supporting Hiv-positive Parentsmentioning
confidence: 99%